Waste management practices of the United States Antarctic Program - Reed, Sherwood C.; Sletten, Robert S.; National Science Foundation (U.S.). Division of Polar Programs.; Cold Regions Research and Engineering Laboratory (U.S.) ([Hanover, N.H.] : US Army Cold Regions Research and Engineering Laboratory, 1989)
"February 1989." Cover title. Bibliography: p. 26. Mode of access: Internet. Water Resources Collections and Archives (WRCA).